2015
DOI: 10.1073/pnas.1513284113
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary transformation of rod photoreceptors in the all-cone retina of a diurnal garter snake

Abstract: Vertebrate retinas are generally composed of rod (dim-light) and cone (bright-light) photoreceptors with distinct morphologies that evolved as adaptations to nocturnal/crepuscular and diurnal light environments. Over 70 years ago, the "transmutation" theory was proposed to explain some of the rare exceptions in which a photoreceptor type is missing, suggesting that photoreceptors could evolutionarily transition between cell types. Although studies have shown support for this theory in nocturnal geckos, the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
96
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 53 publications
13
96
1
4
Order By: Relevance
“…Pituophis melanoleucus inhabits the eastern half of the United States and Canada (Stull, 1940) and spends relatively short intervals on the surface during the day to forage for prey such as small mammals and birds, and to create new burrows (Diller and Wallace, 1996;Himes, 2001). While P. melanoleucus has been found to possess an all-cone retina (Caprette, 2005), similar to previous diurnal colubrid snakes studied (Schott et al, 2016;Sillman et al, 1997), unlike other strongly diurnal colubrids such as the garter snake, P. melanoleucus is more secretive and is thought to spend a considerable amount of time burrowing (Gerald et al, 2006).…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Pituophis melanoleucus inhabits the eastern half of the United States and Canada (Stull, 1940) and spends relatively short intervals on the surface during the day to forage for prey such as small mammals and birds, and to create new burrows (Diller and Wallace, 1996;Himes, 2001). While P. melanoleucus has been found to possess an all-cone retina (Caprette, 2005), similar to previous diurnal colubrid snakes studied (Schott et al, 2016;Sillman et al, 1997), unlike other strongly diurnal colubrids such as the garter snake, P. melanoleucus is more secretive and is thought to spend a considerable amount of time burrowing (Gerald et al, 2006).…”
Section: Introductionsupporting
confidence: 56%
“…Early studies of the colubrid visual system found a green-sensitive visual pigment in addition to a red and a blue pigment (Sillman et al, 1997) in the simplex retina, but were unable to distinguish between a spectrally shifted rhodopsin in a transmuted rod or a potentially resurrected RH2 cone opsin (Cortesi et al, 2015). More recently, a study from our group identified a functional blue-shifted RH1 pigment in the all-cone retina of the ribbon snake (Thamnophis proximus), and proposed that this resulted from a rod to cone evolutionary transmutation in colubrid snakes that may have allowed for enhanced spectral discrimination and even trichromatic colour vision (Schott et al, 2016). A recent study that sequenced the opsins of several other colubrid snake species discovered the widespread presence of full-length rhodopsin genes in species with supposed simplex retinas that were previously presumed to have lost rods or rhodopsins (Simões et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…(reported in [19,20]) detected likely photopic (typical cone) visual pigments identified from their spectral sensitivities by microspectrophotometry (MSP). (iii) Chang and co-workers [21,22] l max values, we suggest the former two are likely LWSand SWS1-based visual pigments, respectively. The l max of the 458 nm pigment suggests either an SWS2-or RH2-based pigment but because neither of these have been found in snakes [10][11][12] we consider it more likely to be an RH1-based pigment (with a lower l max value than is typical for vertebrate RH1-based pigments).…”
Section: Introductionsupporting
confidence: 55%
“…In order to function as a visual rhodopsin, rh1-2 would likely have to be expressed in rods; however, expression in cones is also possible as there are rare cases where rhodopsins and cone opsins are expressed in the opposing photoreceptor type in reptiles and amphibians (Kojima et al, 1992;McDevitt et al, 1993;Schott et al, 2016). While a ∼496 nm peak corresponding to Rh1-2 was not detected in previous microspectrophotometry studies, which could have helped to localize expression at the cellular level (Nawrocki et al, 1985;Robinson et al, 1993;Cameron, 2002), this is likely the result of either a lack of sensitivity to detect the poorly expressing opsin or confounding signals with other opsins that have similar λ max values, such as rhodopsin, Rh2-3 or Rh2-4 (Chinen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%